Generative System for Manufacturing Process Planning - Jan Duda (Communications - Scientific letters of the University of Zilina, 2000)
The paper presents the basic approach for the expert process planning - generative method for planning of the manufacturing processes. The methodology of process plan, structure of manufacturing processes, modelling of processes are key tasks of exact generative methods of creation of process plans. Conclusion of papers describes the expert system EXSYS as a basic tool for development of generative process planning system. In this paper a domain - specific expert system architecture with special emphases put on the control mechanism is presented. Procedurally encoded control mechanism is driven by explicitly represented declarative control knowledge, describing how to use the planning knowledge represented as production rules. On the basis of such knowledge representation three stages were specified: selection of the generalised structure of manufacturing process, reversible design of the semi finished product and intermediate shapes, and generating the machining process. The prototype of an expert system is also presented in this paper. The system combines the rule and frame technique to represent the knowledge and is built using the expert system EXSYS PROFESSIONAL as the shell. It has been verified by building the system which generates process plans for rational parts, manufactured in the CPTOR 1 machining centre.